ANALISA LAPORAN KEUANGAN SEBAGAI BASIS PENGAMBILAN KEPUTUSAN TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PT. PETROKOPINDO CIPTA SELARAS GRESIK (Fakultas Ekonomi Universitas Gresik, 2012)
Levels of the companyÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¢ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¾Ãƒâ€šÃ‚Â¢s ability to continue to compete is determined by the performance of the company itself. The Company is not able to compete in maintaining its performance will gradually displaced from its industrial environment and will face bankruptcy, so that the survival of a company can be reached, then management must improve its performanceThe ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial statements are a source of information about the companyÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¢ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¾Ãƒâ€šÃ‚Â¢s ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial position, performance and changes in ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial position, which is very useful to support decision making. Information presented in order to become more useful in decision making, ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial data must be converted into useful information in making economic decisions. It is reached by way of analyzing the ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial statements.Company performance can be determined from the analysis of ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial statements, ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial statements and analysis to interpretation in essence is to conduct an assessment of potential or ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial performance and progress of a ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ârm through ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial statements, and of those statements can be made through the analysis of ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial ratios. Financial ratio analysis is an alternative to test whether ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial information useful for classiÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Âcation or prediction of a companyÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¢ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¾Ãƒâ€šÃ‚Â¢s ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial condition. Key ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial ratios to be analyzed because of ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial ratios affect the ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial performance of companies that are formed from elements of ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial statements which, when interpreted to obtain information about the companyÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¢ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¾Ãƒâ€šÃ‚Â¢s ÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Ânancial condition in a given period so as to provide input and suggestions for the company.